Implementation of the “Kamoe Sajan Gata” Innovation Towards the Reduction of Maternal Mortality Rate - Muaddah, Muaddah; Pabidang, Siswanto; Pramana, Cipta (Indonesian Journal of Global Health Research, 2024)
Various efforts have been made by the government to achieve the target of reducing maternal and infant mortality rates in Indonesia, but these efforts have not provided maximum results. MMR and IMR are still far from the expectations achieved, this is influenced and driven by various medical and non-medical factors such as lack of support from husbands and families, customs that are still strongly embedded in society and gender factors that still dominate, one of the breakthrough efforts made by the Jeumpa Health Center is the "Kamoe Sajan Gata" innovation, namely accompanying and providing care to high-risk pregnant women from pregnancy to the end of the postpartum period by actively involving cross-sectors as policy makers. Objective to determine the performance of the implementation of the "Kamoe Sajan Gata" innovation on reducing maternal mortality rates in the Jeumpa Health Center work area, Bireuen Regency. This type of research is qualitative with a phenomenology study design. The population of this study were high-risk pregnant women in the Jeumpa Health Center area and across sectors. Research informants 17 people from the elements of the Acting Health Office, Head of Health Center, cross-sector, pregnant women and village midwives, The informant selection technique is purposive sampling. Review of aspects of standards, targets and objectives of the Innovation program policy has been carried out quite well, review of aspects of human resources is not yet fully available, review of aspects of implementer characteristics, review of aspects of communication between implementers and review of aspects of implementer attitudes are very good, and review of environmental aspects, support from all parties is very good while economic support is still very lacking. The performance of the implementation of the Innovation program policy "Kamoe Sajan Gata" has a great influence on efforts to reduce MMR and IMR.